2002
DOI: 10.1097/00007632-200204150-00009
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to False-Versus True-Positive Neuromonitoring Changes in Adolescent Idiopathic Scoliosis Surgery

Abstract: Questions remain about the predictive accuracy of somatosensory-evoked and neurogenic motor-evoked potentials. According to the findings in this study, in which there were no false-negative readings and a modest false-positive rate, continued use of these methods is recommended. Higher false-positive rates were seen in patients with greater lability in mean arterial pressure. A wake-up test is recommended for all cases in which threshold monitoring changes occur because cases of spinal cord injury may exist ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 27 publications
4
33
0
6
Order By: Relevance
“…30,38,45,47 No false negatives were observed and the number of false positives, true positives and true negatives is quite similar to those found in previous studies. [13][14][15]45 In agreement with other authors, [13][14][15]45,48 the persistence of MEPs and/or SEPs correctly predicted the motor or sensory postoperative outcome in our study cohort.…”
Section: Discussionsupporting
confidence: 92%
“…30,38,45,47 No false negatives were observed and the number of false positives, true positives and true negatives is quite similar to those found in previous studies. [13][14][15]45 In agreement with other authors, [13][14][15]45,48 the persistence of MEPs and/or SEPs correctly predicted the motor or sensory postoperative outcome in our study cohort.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, mechanical injury, vascular injury or hypotensive anaesthesia can result in motor changes without concomitant sensory changes in neuromonitoring. The occurrence of transient SEP changes reverting to baseline before the end of surgery is also possible, correlating to postoperative neurologic deficits [16]. Many factors can affect the amplitude and latency of SEP waveforms during surgery [17].…”
Section: Discussionmentioning
confidence: 99%
“…The later developments of the neurophysiological methods clearly indicated that combined application of motor and sensory evoked potentials will increase the validity and reliability of the monitoring techniques and has been advocated by several studies [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…A question about the validity and the predictive accuracy of somatosensory evoked and motor evoked potentials were analysed by following 134 adolescent patients who underwent surgical correction of idiopathic scoliolis [6]. In this study no false negative readings were seen, however, six patients presented false positive findings.…”
Section: Introductionmentioning
confidence: 96%